Characterization of chitosan derived from mushroom sources: Physicochemical, morphological, thermal analysis - Mariah Aqilah Mohd Affandy; Kobun Rovina (Elsevier B.V., 2024)
This research explores chitosan from mushrooms actively cultivated in Malaysia, focusing on its physicochemical, morphological, and thermal properties. The extraction method involves four stages of acid-alkali treatment (HCl and NaOH) with constant conditions across all samples. Chitosan from seven mushroom species and commercially available chitosan (labelled A1 to A8) are compared due to scarce data on mushroom chitosan. Chemical composition results reveal ash (0.65%–3.33%), moisture (4.29%–6.94%), degree of deacetylation (DD%) from 19.15% to 81.94%, and functional group peaks including hydroxyl, amine and carbonyl group. Physical properties present fat binding capacity (FBC) from 354.26% to 649.91%, water binding capacity (WBC) from 124.83% to 522.42%, solubility (50.02%–100.00%), intrinsic viscosity ( ƞ ) from 1.79 dL/g to 5.26 dL/g, average molecular weight (Mv) from 54.26 kDa to 215.26 kDa, and crystallinity index (CrI) from 49.07% to 75.67%. Structural analysis demonstrates rougher surfaces and irregular shapes for the majority of samples. The thermal analysis includes mass loss (68.07%–73.64%), decomposition temperature (220.98 °C–354.29 °C), and glass transition temperature (Tg) from 201.76 °C to 350.94 °C. Overall, mushroom chitosan could serve as an alternative source due to its superior FBC compared to animal-derived chitosan and better thermal stability than commercial chitosan, highlighting its versatility for various applications.